Altered Attainment of Developmental Milestones Influences the Age of Diagnosis of Rett Syndrome - Fehr, S.; Bebbington, A.; Ellaway, C.; Rowe, P.; Leonard, H.; Downs, Jennepher (Sage, 2011)
The early developmental history prior to the manifestation of Rett syndrome features is of clinical interest. This study describes the attainment of gross developmental milestones and regression, and assesses the relationships between genotype and age at diagnosis. The Australian Rett Syndrome Database and International Rett Syndrome Phenotype Database were used to source a total of 293 confirmed female subjects. Most girls learned to sit, were able to babble or use words, and approximately half learned to walk. Altered milestone attainment was associated with earlier diagnosis. There was variation in the acquisition of milestones, the age of regression, and the age of diagnosis by genotype. Most parents expressed concerns about unusual behaviors or development during infancy, and a more subtle atypical development during infancy was reported for most girls. It is important for clinicians to be aware of variable early development in Rett syndrome and that timely genetic testing is not precluded on this account.